Fall 2009 Sabbatical Leave Follow-Up Report - McEachern, Robert (2009)
I was awarded sabbatical leave for Fall 2009. My sabbatical proposal was titled “How Web 2.0 Technologies Are Transforming Writing in Nonprofit Organizations.” My plan, as laid out in my sabbatical proposal, involved tracking and analyzing the online presence of 3-5 nonprofit organizations, and reporting on the ways the nature of their organizational writing had changed, directly and indirectly, as a result of the use of web 2.0 technologies, including blogs, wikis, and social networking sites such as Facebook and Twitter.
Keywords: dept.eng; faculty_collection; sabbatical_report

Bear Country - Sonnenschein, Dana (NFSPS, 2009)
Keywords: Bears; Poetry; dept.eng; faculty_collection

Reflections: neurology and the humanities. You had the choice, Martha. - Shipley, Vivian (Neurology, 2009)
Keywords: *Abortion, Induced/es [Ethics]; *Abortion, Induced/px [Psychology]; *Caregivers/px [Psychology]; *Lesch-Nyhan Syndrome/ge [Genetics]; *Maternal Behavior/px [Psychology]; *Neurology/es [Ethics]; Abortion, Induced; Adult; Caregivers; Choice Behavior; Choice Behavior/es [Ethics]; Female; Humans; Infant; Lesch Nyhan syndrome; Lesch-Nyhan Syndrome; Lesch-Nyhan Syndrome/pp [Physiopathology]; Male; Maternal Behavior; Muscle Weakness; Muscle Weakness/ge [Genetics]; Neurology; Poetry as Topic; Self-Injurious Behavior; Self-Injurious Behavior/ge [Genetics]; Self-Injurious Behavior/pc [Prevention & Control]; adult; article; automutilation; caregiver; decision making; dept.eng; ethics; female; genetics; human; induced abortion; infant; literature; male; maternal behavior; muscle weakness; neurology; pathophysiology; psychological aspect

The letter and the law, or how caroline norton (Re)Wrote female subjectivity - Fluhr, Nicole (Tulsa studies in women's literature, 2009)
Keywords: dept.eng; ⛔ No DOI found